Salivary cortisol, heart rate, and blood lactate responses during elite downhill mountain bike racing - Sperlich, B.; Achtzehn, S.; Buhr, M.; Zinner, C.; Zelle, S.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2012)
Purpose: This study aimed to quantify the intensity profile of elite downhill mountain bike races during com- petitions. Methods: Seventeen male downhill racers (22 ± 5 y; 185.1 ± 5.3 cm; 68.0 ± 3.9 kg; VO2peak: 59.4 ± 4.1 mL/min·kg) participated in the International German Downhill Championships in 2010. The racers` peak oxygen uptake and heart rate (HR) at 2 and 4 mmol/L blood lactate (HR2 and HR4), were assessed during an incremental laboratory step test (100 W, increase 40 W every 5 min). During the races, the HR was recorded and pre- and postrace blood lactate concentrations as well as salivary cortisol levels were obtained. Results: During the race, the absolute time spent in the "easy" intensity zone was 23.3 ± 6.8 s, 24.2 ± 12.8 s (HR2-HR4) in the "moderate" zone, and 151.6 ± 18.3 s (>HR4) in the "hard" zone. Eighty percent of the entire race was accomplished at intensities >90% HRpeak. Blood lactate concentrations postrace were higher than those obtained after the qualification heat (8.0 ± 2.5 mmol/L vs 6.7 ± 1.8 mmol/L, P < .01). Salivary levels of cortisol before the competition and the qualification heat were twice as high as at resting state (P < .01). Conclusions: This study shows that mountain bike downhill races are conducted at high heart rates and levels of blood lactate as well as increased concentration of salivary cortisol as marker for psycho-physiological stress.